EFFECT OF FLUORIDE SOLUTION ON SALIVARY AMYLASE ACTIVITY - Willianti, Enny (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2015)
Fluoride has the benefit on the tooth to inhibit caries. Fluoride is systemically incorporated into the crystal lattice of enamel by exchanging positions with the hydroxyl ion to result in formation of fluorapatite. Fluoride used locally may inhibit tooth demineralization, one of the mechanism is that fluoride is suspected to inhibit salivary amylase activity.The aim of this research is to exam whether fluoride inhibits salivary amylase activity and at what concentration.Method of this research was experimental research and the design was "The posttest only control group design". The samples were taken from patients with criteria: man or woman, 13-20 years old, in fit condition, no salivary gland disorder, no caries, no gingivitis. Saliva was collected from samples fasted in the night, and asked to brush their teeth without using toothpaste. This experiment used iodium to detect the color reaction. The method also used NaF with several concentrations in saliva.The result of this experiment indicated that almost all groups have a statistically significant differences salivary amylase activity (p<0,05), except between the group without NaF and with 1 mM NaF and 2 mM NaF, betweenl mM NaF and 2 mM NaF, between 2 mM NaF dan 5 mM NaF, between 5 mM NaF and 10 mM NaF (p>0,05).Conclusion of this research found that NaF was found to inhibit the salivary amylase activity when the fluoride concentration was at and above 5 mM.